Investigating the Impact of Reproductive Coercion and Intimate Partner Violence on Psychological and Sexual Wellbeing - Sheeran, Nicola (Journal of interpersonal violence, 2025)
Emerging research suggests that reproductive coercion and abuse (RCA), like intimate partner violence (IPV), is associated with poorer mental and sexual health outcomes, including greater symptoms of post-traumatic stress disorder (PTSD) and depression and poorer markers of physical and sexual health such as sexually transmitted infections, unplanned pregnancies and lowered sexual agency. Although victims/survivors of RCA report long-lasting impacts on future relationships, including fear and anxiety, little is known about impacts of RCA on anxiety and general wellbeing, nor emotional and mental components of sexual health that comprise a person’s sexual self-concept. With community samples of participants in Australia, we conducted two studies to explore the impact of RCA and IPV on psychological (study 1) and sexual (study 2) health outcomes. Study 1 (n = 368) found that experiencing IPV and RCA both significantly and uniquely contributed to poorer mental health outcomes. After controlling for age and IPV, RCA significantly predicted symptoms of depression, anxiety, stress, PTSD, and reduced satisfaction with life. Study 2 (n = 329) found that IPV and RCA differentially predicted various components of sexual health. IPV predicted decreased sexual satisfaction and increased sexual anxiety, depression, and fear of sexual encounters. After controlling for age and IPV, RCA significantly and uniquely predicted lower levels of sexual assertiveness and increased sexual depression and fear of sexual encounters, but not sexual satisfaction or anxiety. We conclude that RCA is associated with significant psychological distress and a negative sexual self-concept that may impact future relationships. Screening for both IPV and RCA across settings is warranted.